Parasexual reproduction in Alternaria solani: Simple sequence repeat molecular evidence for haploidization. (3rd September 2021) - Zhao, Dongmei; Fan, Shasha; Zhang, Dai; Pan, Yang; Gu, Qing; Wang, Jinhui; Yang, Zhihui; Zhu, Jiehua
ABSTRACT: Multiple alleles were constantly detected in Alternaria solani isolates by simple sequence repeat (SSR) analysis, and sectors were also observed in their subcultures. These preliminary results and observations point to a possible parasexual cycle in A. solani . In this study, codominant SSR markers were used as molecular markers on the chromosomes of A. solani and single-conidium subculture was used to simulate the mitosis process of A. solani in nature. The number of alleles at locus As-95236 changed from 2 to 1 as a molecular marker for haploidy of parasexuality of A. solani . Fifty monosporic F1 strains were tested. The results showed that two parent strains lost allele with a haploid probability of 38%. For F2 strains, the results showed that all four F1 strains lost allele with a haploid probability of 75%. Since sexual recombination of A. solani has not been found so far, the allele lost in the subcultures of A. solani isolates provides molecular evidence for the existence of parasexual reproduction in A. solani .